MATHEMATICAL FORMULATION OF THE AIRCRAFT MAINTENANCE PROGRAMME PROBLEM - Ліннік, О. П. (Science-based technologies, 2013)
The article deals with basic questions of improving the methodology of aircraft maintenance program development in operation and the principles of mathematical model of control of transport aircraft maintenance program were proved. These principles are based on theoretical generalizations related to the study of manufacturing processes in the aircraft maintenance.